2019
DOI: 10.3847/1538-3881/ab5220
|View full text |Cite
|
Sign up to set email alerts
|

K2-19b and c are in a 3:2 Commensurability but out of Resonance: A Challenge to Planet Assembly by Convergent Migration

Abstract: K2-19b and c were among the first planets discovered by NASA's K2 mission and together stand in stark contrast with the physical and orbital properties of the solar system planets. The planets are between the size of Uranus and Saturn at 7.0 ± 0.2 R ⊕ and 4.1 ± 0.2 R ⊕ , respectively, and reside a mere 0.1% outside the nominal 3:2 mean-motion resonance. They represent a different outcome of the planet formation process than the solar system, as well as the vast majority of known exoplanets. We measured the phy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 79 publications
3
25
0
Order By: Relevance
“…The mean and 1σ range of f env,0 inferred when neglecting tides are shown with the gray line and bar. The tides-free envelope fraction estimates are f env,0 =44.2%±2.8% for K2-19 b and f env,0 =14.2%±2.0% for K2-19 c, which are both consistent with the estimates from Petigura et al (2020). The agreement is reassuring, given that these estimates were obtained with two distinct core-envelope models.…”
Section: Inferences Of F Env When Including Tidessupporting
confidence: 76%
See 3 more Smart Citations
“…The mean and 1σ range of f env,0 inferred when neglecting tides are shown with the gray line and bar. The tides-free envelope fraction estimates are f env,0 =44.2%±2.8% for K2-19 b and f env,0 =14.2%±2.0% for K2-19 c, which are both consistent with the estimates from Petigura et al (2020). The agreement is reassuring, given that these estimates were obtained with two distinct core-envelope models.…”
Section: Inferences Of F Env When Including Tidessupporting
confidence: 76%
“…Many sub-Saturns have such large radii and low masses that standard core-envelope structural models have suggested that they must have massive atmospheric envelopes comprising ∼50% of their total mass (e.g., Petigura et al 2018aPetigura et al , 2020Addison et al 2020). This posed a problem for the theory of core accretion, which dictates that planets undergo runaway gas accretion when their envelope mass reaches their core mass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In exceptional cases, important additional insight into the orbital machinery of a given system can be gleaned from combined transit timing analysis and radial velocity measurements (Petigura et al 2018(Petigura et al , 2020. Direct characterization aside, however, a thornier question concerns how orbital layouts of extrasolar planets arise in the first place.…”
Section: Introductionmentioning
confidence: 99%